Procrastination: ways of prophylaxis, prevention (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article considers the phenomenon of procrastination in thecontext of different cultures and time. The concept of “procrastination”is investigated; the relevance of this phenomenon and the laws of itsgrowth are determined. The results of an empirical study of the spreadof this phenomenon among young people are presented. The reasonsfor the existence of procrastination in adolescence are clarified. Factorscontributing to an increase in the level of procrastination have identified.Highlighted modern approaches to the problem and described the maintypes of procrastination. The mechanism of its work is shown and themain types of procrastinators are presented. A list of distractions has beencompiled and psychological-pedagogical recommendations developed toprevent procrastination.
Keywords: procrastination; procrastinator; stress; motivation; youthful period; youth